Соціально-правовий захист учасників бойових дій в Україні : автореф. дис. - Панченко, Г. В.; Panchenko, H. V. (Харків, 2018)
У дисертації на підставі узагальнення наукових праць вчених, а також сучасної нормативно-правової бази визначено сутність та особливості соціально-правового захисту учасників бойових дій в Україні. Розкрито сутність поняття учасника бойових дій. Окреслюються загальні засади правового статусу учасників бойових дій. Характеризується стан нормативно-правового забезпечення соціально-економічних інтересів учасників бойових дій Україні. Узагальнюється зарубіжний досвід забезпечення соціально-економічних інтересів учасників бойових дій. З’ясовуються проблеми функціонування та розвитку системи соціально-правового захисту учасників бойових дій. Опрацьовуються практичні рекомендації щодо вдосконалення нормативної бази та системи соціально-правового захисту учасників бойових дій.

The essence and peculiarities of social and legal protection of the participants of military operations in Ukraine have been determined in the dissertation on the basis of generalization of scientific works of scholars, as well as the modern legal and regulatory base. The author has revealed the essence of the concept of a participant of military operations. The general principles of the legal status of the participants of military operations have been outlined. The author has characterized the state of regulatory provision of socio-economic interests of the participants of military operations in Ukraine. International experience of providing socio-economic interests of the participants of military operations has been generalized. The problems of the functioning and development of the system of social and legal protection of the participants of military operations have been clarified. Practical recommendations for improving the regulatory base and the systems of social and legal protection of the participants of military operations have been studied.

В диссертации на основании обобщения научных трудов ученых, а также современной нормативно-правовой базы определена сущность и особенности социально-правовой защиты участников боевых действий в Украине. Раскрыта сущность понятия участника боевых действий. Определяются общие принципы правового статуса участников боевых действий. Характеризуется состояние нормативно-правового обеспечения социально-экономических интересов участников боевых действий Украины. Обобщается зарубежный опыт обеспечения социально-экономических интересов участников боевых действий. Выясняются проблемы функционирования и развития системы социально-правовой защиты участников боевых действий. Прорабатываются практические рекомендации по совершенствованию нормативной базы и системы социально-правовой защиты участников боевых действий.
Автореферат дисертації на здобуття наукового ступеня кандидата юридичних наук
Social and Legal Protection of the Participants of Military Operations in Ukraine
Панченко, Г. В. Соціально-правовий захист учасників бойових дій в Україні : автореф. дис. ... канд. юрид. наук : 12.00.05 / Г. В. Панченко; МВС України, Харк. нац. ун-т внутр. справ. - Харків, 2018. - 15 с.
Keywords: Трудове право. Право соціального забезпечення. Labor law. Law of social guaranteeing. Трудовое право. Право социального обеспечения; Автореферати дисертацій. Abstracts of Theses. Авторефераты диссертаций; Україна. Ukraine. Украина; 12.00.05; соціально-правовий статус; социально-правовой статус; social and legal status; правовий захист; правовая защита; соціальний захист; социальная защита; social security; учасник бойових дій; участник боевых действий; participant in military operations; зарубіжний досвід; зарубежный опыт; foreign experience